KERJASAMA PEMERINTAH DESA DAN BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN DESA DI DESA WOLWAL DAN DESA WOLWAL TENGAH KECAMATAN ALOR BARAT DAYA KABUPATEN ALOR - Elvina Elsanda Moy; Rafael Rape Tupen; Cyrilius Wilton Taran Lamataro (Petitum Law Journal, 2026)
This study examines the collaboration between the Village Government and the Village Consultative Body in village development in Wolwal and Wolwal Tengah villages, Alor Barat Daya District, Alor Regency. Using empirical legal methods including field observations, in-depth interviews with village heads, village consultative body members, and community leaders, and document analysis this study identifies patterns of collaboration in planning, implementing, monitoring, and evaluating development programs. The results show that although formal collaboration follows the principles of partnership, consultation, and coordination through participatory forums (Musdus, Musdes, Musrenbang), there are still major challenges that need to be addressed: (1) weak coordination and differences in priorities between the village head and village consultative body; (2) shallow community participation; (3) limited human resource capacity (most officials only have a high school education); (4) inadequate infrastructure (e.g., uncertified village offices, damaged facilities); and (5) non-independent village consultative body supervision. This study concludes that to optimize development outcomes, it is necessary to strengthen institutional capacity, increase community involvement, and have a more professional monitoring mechanism to achieve transparent, accountable, and sustainable village governance.